Directions for the development of socially oriented taxation of income of Russians - S. N. Rukina; K. A. Gerasimova; A. S. Takmazyan; K. N. Samoylova (Вестник университета)
Personal income tax (hereinafter referred to as PIT), in interaction with other instruments, can have a significant impact on the implementation of social goals aimed at improving the quality of life of Russians, reducing poverty, overcoming monetary inequality, and supporting low-income citizens, including families with children. The article is aimed at studying the theoretical and practical aspects of taxation of personal income regulated by Chapter 23 of the Russian Tax Code. It reveals the significant role of the PIT due to its revenue potential for the budget system of the Russian Federation and its regulatory impact on socio-economic processes in conditions of geopolitical tension, describes the current system of tax deductions, the need and directions for its improvement. The methodological basis of the study is founded on the analysis of scientific publications and open data of public authorities posted on their official websites. The analysis has been conducted using comparison methods, systemic logical and semantic analysis, synthesis of theoretical and practical material. The purpose of the study is to propose a gradual improvement of the mechanisms for providing standard and social tax deductions by increasing their sizes, introducing a subsistence minimum as a non-taxable income for all categories of payers, expanding the scope of application with consideration to the results of the ongoing socio-economic policy. The conclusions and generalisations of the study can be used when legislative and executive authorities and the scientific community develop proposals for improving the provisions of Chapter 23 of the Russian Tax Code, which will create a socially oriented domestic tax system.